Estimation of heterosis and combining ability for yield and yield- attributing traits in spine gourd (Momordica dioica) - Sandilya, Vivek; Bhagat, Sanjay; Jyoti Bajeli; Arunima Tripathi; S. K. Sinha; Jitendra Kumar Tiwari (Current Horticulture, 2025)
Heterosis for quantitative characters in 31 spine gourd genotypes, including 10 parents and 21 F1s, was investigated in spine gourd (Momordica dioica Roxb.) during 2016-2018. Analysis of variance revealed highly significant differences among parents and hybrids for 10 characters. Considerable coefficient of variation for various characters was observed to distinguish among various genotypes. The cross, NDM-5 x AJSG-2, showed heterosis over mid-parent and NDM-5 x AJSG-2 over better parent for single fruit weight. Crosses Ambika 13-5 X Chhattisgarh Kankoda-2 (69.24 q/ha), Ambika 13-6 X AJSG-2 (68.30 q/ha), RMDSG-4 x Chhattisgarh Kankoda-2 (66.60 q/ha), NDM-5 X AJSG-2 (66.19 q/ha), RMDSG-3 X Chhattisgarh Kankoda-2 (62.89 q/ha), AJSG-1 x IK-1 (61.47 q/ha), NDM-5 X IK-1 (59.26 q/ha), Ambika 13-5 X AJSG-2 (58.15 q/ha) and RMDSG-3 X IK-1 (55.56 q/ha) can be used to get good heterotic combination and it will be multiply through stem cuttings after fixation of heterosis in the form of asexual propagating material, i.e. tubers. Therefore, these cross combinations could be utilized in isolation of superior parents for incorporating yieldattributing and qualitative traits in spine gourd.